Illuminating the “black box” of complex suicide prevention interventions: towards a theory of implementation using the normalisation process theory - Sadhvi Krishnamoorthy; Gregory Armstrong; Sharna Mathieu; Victoria Ross; Kairi Kõlves (Frontiers in Health Services)
IntroductionAlthough there has been some investigation into what works in suicide prevention, exploration into the mechanisms by which implementation strategies impact outcomes or how and why strategies work remains largely under-studied. Consequently, implementation efforts often lack a clear strategy, and may contribute little toward the desired outcomes. This study aims to explore and examine the role of context and mechanisms involved in the implementation of complex suicide prevention interventions.Methods and materialsIn-depth qualitative interviews were used to explore relevant stakeholder experiences of implementing complex suicide prevention interventions. Stakeholders (nine intervention leaders, five implementors and two lived experience advocates) from six interventions were purposively recruited for their experiences involved in implementing complex interventions in real-world settings. The Normalisation Process Theory translational coding manual was used to map data related to the primary and secondary constructs defined in the theory and its extensions.ResultsThree domains pertaining to implementation context, mechanisms, and outcomes (CMO) were explored. Participants expressed their agency by: using contextual influences to modify the design and plan for delivery; making adaptations to the form and function of interventions and characteristics of the implementation environment to suit intervention needs; and, leveraging the intervention environment to integrate the intervention into existing systems and practices. Activities and strategies served multiple mechanisms involved in: understanding what the work entails; who does the work; developing the capacity to implement the work; and, understanding the work. An interdependent and interacting relationship between mechanisms emerged. Outcomes related to: change in existing practices; the ways in which people are organised; changes in existing norms; and, incorporation of the intervention into daily practice were observed.ConclusionThis study is notable in its exploration of mechanisms underlying implementation of complex suicide prevention interventions. Data from this study can help inform the development, refinement and use of specific implementation strategies and understand the applicability of strategies across varied contexts. The study also demonstrates the use of an implementation theory to inform practice and potentially contributes to an understanding of what works, why, for whom and in what context. There is a need for a paradigm shift towards the use of more theory based and informed approaches to understand causal links between implementation strategies, context, mechanisms, and outcomes.